2021
DOI: 10.1177/2150135120975769
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Heterotopic Placement of Right Ventricle to Pulmonary Artery Conduits

Abstract: Background: We sought to evaluate the outcomes following right ventricle to pulmonary artery (RV-PA) conduit placement in pediatric patients, excluding those with a RV-PA conduit for the Ross procedure which is associated with improved conduit durability, partly related to its orthotopic position. Methods: Outcomes for 119 patients who underwent RV-PA conduit placement at a single institution from January 2004 to December 2016 were reviewed. Primary outcome measures were reintervention-free survival (RFS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Even though our results did not show pulmonary homograft to be superior in terms of conduit dysfunction-free, reintervention-free, and overall survival, we still preferred pulmonary homograft to be the conduit of choice at our institution. One study 12 mentioned that immune process had a more prominent role in causing conduit dysfunction in children than in adults. However, from our results, we found that younger age at operation did not adversely affect conduit longevity, reintervention-free survival, and overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though our results did not show pulmonary homograft to be superior in terms of conduit dysfunction-free, reintervention-free, and overall survival, we still preferred pulmonary homograft to be the conduit of choice at our institution. One study 12 mentioned that immune process had a more prominent role in causing conduit dysfunction in children than in adults. However, from our results, we found that younger age at operation did not adversely affect conduit longevity, reintervention-free survival, and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nal results varied widely, and de nite risk factors or determinants of conduit longevity, reintervention-free survival, and overall survival still could not be precisely de ned. Furthermore, not only conduit position but also conduit types and sizes could impact their durability and patient's reintervention-free and overall survival 5,8,9,[12][13][14][16][17][18] . However, most of the results contradicted each other, with no clear consensus made.…”
Section: Introductionmentioning
confidence: 99%
“…No commercially available PPVRs are ideal and RVOT reconstruction will often require repeat operations later in life to replace dysfunctional prosthetics 18,19 . Importantly, freedom from RVOT reoperation varies depending on the clinical context, influenced by factors such as CHD etiology, age at implantation and PPVR type, as well as institutional and patient preferences.…”
Section: Reoperation Requirementsmentioning
confidence: 99%
“…Many CHDs affect the right ventricular outflow tract (RVOT) (Table 1), leading to a significant requirement for pulmonary valve (PV) replacement in the pediatric population 12–15 . The PV is one of four heart valves that mediate a strict unidirectional blood flow through the heart 16,17 ; however, the lack of ideal replacement prosthetics generates a requirement for repeat interventions throughout early life 18,19 . Prosthetics based on metals are prone to thrombosis and require lifelong anticoagulation, introducing additional burdens that persist past childhood, 20,21 while those based on biological materials exhibit underwhelming durability due to their immunogenicity and structural degradation 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Bioprostheses and homografts are susceptible to immune responses and structural valve deterioration [3]. Unfortunately, these poor outcomes tend to manifest earlier for younger patients, forcing them to undergo multiple operations throughout their lifetime [4][5][6].…”
Section: Introductionmentioning
confidence: 99%